Bioprocessing of Agro-Industrial Waste for Maximization of Pectinase Production by a Novel Native Strain Aspergillus cervinus ARS2 Using Statistical Approach - Anil R. Shet; Abdullatif Bin Muhsinah; Abdulfattah Y. Alhazmi; Sharanappa Achappa; Shivalingsarj V. Desai; Mater H. Mahnashi; Uday M. Muddapur; Aejaz Abdullatif Khan; Ibrahim Ahmed Shaikh (Separations, 2022)
The demand for microbial pectinase has increased due to its vast applications in different industries. The current study dealt with the synthesis of pectinase by a novel native strain Aspergillus cervinus ARS2 using agro-industrial waste. Comparative studies conducted on pectinase production by submerged fermentation (SmF) and solid-state fermentation (SSF) showed that pectinase activity was more increased in SSF (44.51 ± 1.33 IU/mL) than in SmF (40.60 ± 1.15 IU/mL) when using orange peel as a substrate. Using SSF, one-factor-at-a-time (OFAT) studies were conducted, considering different process variables such as inoculum size, initial pH, incubation time, moisture content, incubation temperature, and substrate particle size, all of which affected the pectinase activity. OFAT results showed the highest pectinase activity at an inoculum size of 106 spores/mL (43.11 ± 1.06 U/mL), an incubation time of 6 days (43.81 ± 1.21 U/mL), a moisture content of 100% (44.30 ± 1.69 U/mL), a substrate particle size of 1.7 mm (42.06 ± 1.20 U/mL), an incubation temperature of 37 °C (45.90 ± 1.33 U/mL), and an initial pH of 4 (43.31 ± 0.89 U/mL). The identified significant process variables were then optimized by response surface methodology (RSM)-central composite design (CCD). The results showed optimum pectinase activity of 107.14 ± 0.71 IU/mL for a substrate particle size of 2 mm, an incubation temperature of 31.5 °C, an initial pH of 4.9, and a moisture content of 107%, which was obtained from the Minitab optimizer. By using statistical optimization, the pectinase production from the isolated novel fungal strain A. cervinus ARS2 was increased 2.38-fold. Therefore, the A. cervinus ARS2 strain can be further explored for large-scale pectinase production which could meet the growing industrial demands.